Protecting Stem Cell Derived Pancreatic Beta-Like Cells From Diabetogenic T Cell Recognition - Castro-Gutierrez, Roberto; Alkanani, Aimon; Mathews, Clayton E.; Michels, Aaron; Russ, Holger A. (Frontiers in Endocrinology, 2021)
Type 1 diabetes results from an autoimmune attack directed at pancreatic beta cells predominantly mediated by T cells. Transplantation of stem cell derived beta-like cells (sBC) have been shown to rescue diabetes in preclinical animal models. However, how sBC will respond to an inflammatory environment with diabetogenic T cells in a strict human setting has not been determined. This is due to the lack of model systems that closely recapitulates human T1D. Here, we present a reliable in vitro assay to measure autologous CD8 T cell stimulation against sBC in a human setting. Our data shows that upon pro-inflammatory cytokine exposure, sBC upregulate Human Leukocyte Antigen (HLA) class I molecules which allows for their recognition by diabetogenic CD8 T cells. To protect sBC from this immune recognition, we utilized genome engineering to delete surface expression of HLA class I molecules and to integrate an inducible overexpression system for the immune checkpoint inhibitor Programmed Death Ligand 1 (PD-L1). Genetically engineered sBC that lack HLA surface expression or overexpress PD-L1 showed reduced stimulation of diabetogenic CD8 T cells when compared to unmodified cells. Here, we present evidence that manipulation of HLA class I and PD-L1 receptors on sBC can provide protection from diabetes-specific immune recognition in a human setting.